Virtual Reality – 1 Project - 13 Museums - Ulrike Braun (EXARC Journal)
Visitors in 13 museums in the rural area around the city of Lüneburg (Lower Saxonia, Germany) can now discover different aspects of the interrelationship between man and nature within a virtual world. Six themes or titles guide through to whole story, like nature means threat, or nature means work or beauty, etc. symbolised by a silhouette.